Chapter 2. Sample Preparation Techniques (Analytical Methods for Drug Development, 2025)
AuthorDr. Praveen Kumar BorraAssociate Professor, Department of Pharmaceutical Chemistry, Sultan-ul-Uloom College of Pharmacy, Banjara Hills, Hyderabad, Telangana, IndiaAbstractSample preparation directly impacts analytical method accuracy and sensitivity, serving as a critical pre-analytical phase. Extraction methodologies encompass liquid-liquid extraction, solid-phase extraction, and microextraction techniques, each with specific protocols for pharmaceutical applications. Matrix interference in biological samples, plasma, and complex formulations requires targeted strategies to minimize their impact on analytical results. Modern sample preparation incorporates automation, miniaturization, and green chemistry principles for sustainable processing with reduced solvent consumption. Sample stability during processing involves temperature control, light protection, and chemical degradation prevention to maintain analyte integrity. Optimization strategies improve extraction efficiency, enhance selectivity, and maximize concentration factors for trace analysis. Method validation for sample preparation includes recovery studies, matrix effects assessment, and stability evaluation during processing.Keywords: Extraction Methods, Matrix Interference, Automated Sample Preparation, Green Extraction Techniques, Sample Processing ValidationVIEW PDF